Analisis Pengaruh Current Ratio, Return on Equity dan Debt to Equity Ratio Terhadap Return Saham Pada Perusahaan Sub Sektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Elida Gultom; Kartika Sari Lubis (ARBITRASE: Journal of Economics and Accounting, 2021)
The high demand for telecommunications networks and internet data in the community has caused telecommunications companies to become one of the targets for investors, but not all companies can provide stock returns as expected. This study aims to determine the effect of the current ratio, return on equity and debt to equity ratio on stock returns either simultaneously or partially in Telecommunication Sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study are all Sub-sector companies. The Telecommunications sector listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, amounting to 6 companies. The sample was carried out by purposive sampling technique with a sample of 4 companies. This research method uses survey research with a quantitative approach. The data analysis technique used is Multiple Linear Regression. The conclusion of this study is that the current ratio, return on equity and debt to equity ratio simultaneously have a significant effect on stock returns. Current ratio and Dept to equity ratio (DER) have no effect on stock returns, while return on equity (ROE) has no effect on stock returns. The magnitude of the influence of the current ratio, return on equity (ROE) and debt to equity ratio on stock returns is 43.3%. And the variable that has the most influence on stock returns in Telecommunication Sub-Sector companies on the Indonesia Stock Exchange (IDX) for the period 2015 to 2019 is return on equity (ROE)